Double Phase Phenomena in Navier Boundary Problems with Degenerated $(p(.), q(.))$-Operators (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we are interested in some results of the existence ofmultiple solutions for Navier boundary value problem involving degenerated $(p(.), q(.))$-Biharmonic and $(p(.), q(.))$-Laplacian operators. Our approach isbased on variational method and critical point theory.